Ensino coletivo de violão em um assentamento do movimento dos trabalhadores rurais sem terra - Chagas, Anderson Moisés Barbosa Souza (2020)
The present work proposes an investigation on educational processes arising from the social practice of collective guitar teaching in a Landless Workers' Movement - MST, located in the city of Serra Azul - SP. We understand that educational processes are inherent to, and at the same time, social practices. In this context, and with the perspective that many learnings can arise from the coexistence between the participants, we will seek to answer the research questions related to: what are the educational processes arising from the social practice of collective guitar teaching in the MST Settlement? How can these processes become a potential for teaching and learning? To this end, as an objective I sought to identify, describe and understand the possible educational processes arising from collective guitar teaching. The search for results took place through the participatory research methodology, in which the data collection started from an insertion in the time space of the classes, during the performance of daily activities. As a memory resource, field diaries were used during the data collection and insertion period. We believe that research can contribute to the production and construction of knowledge related to music education, social practices and educational processes, as it has evidenced educational processes related to: learning from each other; autonomy and protagonism. The analysis of the aforementioned educational processes contributed to the understanding of the importance of developing a humanizing educational praxis, in the most diverse work environments that a musical educator may be inserted in.